(untitled) (Journal of the College of Basic Education, 2022)
The research included five chapters, the first chapter included the introduction and the importance of the research, as the importance of using functional strength training was clarified in the side of the basketball game, and the research problem appeared through the researchers’ follow-up to the reality of our matches at the level of local clubs. And the weak skill of scoring from jumping, and because the two researchers are interested in the sport of basketball, they decided to design a functional strength training program in a serious attempt to develop scoring skills from jumping and peaceful scoring with basketball. basket,